EFEKTIVITAS PESAN KAMPANYE BKKBN #BERENCANAITUKEREN SEBAGAI PENYEDIA INFORMASI DAN EDUKASI KB TERHADAP SIKAP KHALAYAK (Survey Pada Pengikut Akun Instagram @bkkbnofficial) - Raihan Ismail, (2022)
As we all know, the largest population in Southeast Asia, namely Indonesia, can be seen from the increasing population census (Kompas, 2021). Therefore, the BKKBN was formed as an institution that regulates to carry out government duties in the field of family planning and prosperous families. In this study, the author uses a survey method. The purpose of using this explanative quantitative survey method is to explain the relationship between the second variable, to know the audience's attitude towards the #BeplanningIuKeren campaign message. The analysis technique used is probability sampling technique with simple random sampling method. The author explains how effective the campaign message of the BKKBN #PlanituKeren is as a provider of information and education to followers of the @bkkbnofficial Instagram account carried out by the Public Relations of the Family Population and Planning Agency. Researchers must take a sample of data from followers of @bkkbnofficial to continue research and find out the results of this study. The results of this survey can provide information regarding the effectiveness of the BKKBN family planning program on the level of public interest in participating in the program. Based on the results of the study, it can be said that the effectiveness of the #BeituKeren BKKBN campaign message in providing information and education to the public through the @bkkbnofficial Instagram account is very good with an average consideration of 97.46% in the very good category. A very significant influence was found on the #planningitukeren campaign message on public attitudes. It was found that cluster 1 has 68 members, cluster 2 has 71 members, cluster 3 has 71 members and cluster 4 has 69 members. Based on the rule of thumb which states that a cluster can be considered an outlier if it has 5% members of the total data. The use of social media is important in conducting campaigns.